Musculoskeletal Ultrasound for Preoperative Imaging of the Plantar Plate: A Prospective Analysis. Issue 3 (June 2013) - Klein, Erin E.; Weil, Lowell; Weil, Lowell Scott; Knight, Jessica
The purpose of this study was to prospectively compare preoperative findings on musculoskeletal ultrasound evaluation to observed intraoperative findings for patients undergoing surgical correction of plantar plate tears. Fifty consecutive patients with forefoot pain and a suspected unilateral plantar plate tear at the second metatarsophalangeal (MTP) joint were identified. The same examiner performed a 2-plane (longitudinal and transverse) musculoskeletal ultrasound on the painful second MTP joint. The contralateral second MTP joint was used for comparison. Longitudinal ultrasound images were graded as "torn" or "intact." Transverse ultrasound images were used to localize the suspected pathology. Results of the ultrasound were compared with observed intraoperative pathology. Forty-five plantar plate tears were identified intraoperatively. Longitudinal ultrasound images correctly identified 40 plantar plate tears. The longitudinal ultrasound had a sensitivity of 91.1%, a specificity of 25%, a positive predictive value of 91.1%, and a negative predictive value of 25%. Transverse ultrasound images identified 36 plantar plate tears correctly localizing only 19 tears. Musculoskeletal ultrasound has been widely used to identify and localize pathology in many soft tissue structures. Whereas the longitudinal ultrasound images were useful in identifying plantar plate tears, the same cannot be said about the ability to localize the tear on the transverse ultrasound images. Therefore, ultrasound may not be as good an imaging modality as magnetic resonance imaging for identification and localization of plantar plate pathology. Levels of Evidence: Diagnostic, Level II